2022
DOI: 10.1055/s-0041-1740623
|View full text |Cite
|
Sign up to set email alerts
|

Has the COVID-19 Pandemic Impacted Interest in Cosmetic Facial Plastic Surgery? A Google Trends Analysis

Abstract: Facial cosmetic surgery trends are evolving in the current climate of the coronavirus disease 2019 (COVID-19) pandemic. The aim of this study was to evaluate public interest in elective facial plastic surgery during the COVID-19 pandemic including the period of the COVID-19 vaccine distribution using Google Trends. A Google Trends analysis was completed using popular terms related to facial cosmetic surgery and procedures from March 2017 to August 2021. Three stages were identified (baseline, pre-COVID-19 vacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 12 publications
2
17
0
Order By: Relevance
“…10 In addition, patients who were previously hesitant to undergo cosmetic surgery now had more postoperative recovery time: working from home, social distancing, and use of masks in public settings minimized social judgments relating to bruising and swelling. 20,21 Stimulus checks and reduced expenses from lack of social gatherings could have further motivated patients to undergo cosmetic procedures. 21 Rises in social media engagement, as observed during the COVID-19 pandemic, are associated with more body and facial dissatisfaction, along with depression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 In addition, patients who were previously hesitant to undergo cosmetic surgery now had more postoperative recovery time: working from home, social distancing, and use of masks in public settings minimized social judgments relating to bruising and swelling. 20,21 Stimulus checks and reduced expenses from lack of social gatherings could have further motivated patients to undergo cosmetic procedures. 21 Rises in social media engagement, as observed during the COVID-19 pandemic, are associated with more body and facial dissatisfaction, along with depression.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Stimulus checks and reduced expenses from lack of social gatherings could have further motivated patients to undergo cosmetic procedures. 21 Rises in social media engagement, as observed during the COVID-19 pandemic, are associated with more body and facial dissatisfaction, along with depression. 16 A cross-sectional survey-based study demonstrated that viewing cosmetic surgery-related content on social media, spending longer hours on these platforms, and possessing negative self-images are associated with an increased likelihood of undergoing future cosmetic procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The perioral region is significant in conveying one’s age, contributing to facial attractiveness and beauty [ 1 5 ], and is gaining more interest during the COVID-19 pandemic [ 6 ]. A youthful and attractive perioral region consists of a relatively shorter upper lip with soft tissue projection [ 7 , 8 ] whereas the most significant senile alterations are upper lip lengthening and shape deformities [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aesthetic and cosmetic procedure demand demonstrates solid global growth. This growth has been observed mainly after lockdown measures were relaxed, together with reinforcement of all necessary post-coronavirus disease 2019 (COVID-19) precautions for a safe environment [ 1 , 2 ]. Different factors attributed to the pandemic influence have been linked to the rise in aesthetic procedures, including the use of video conferencing platforms for work, school, telemedicine, and socialization [ 1 , 3 ].…”
Section: Introductionmentioning
confidence: 99%